Perancangan Budaya Kerja 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) di PT. Andalas Citra Elektrindo - Pangaribuan, Rafiq Kurnia; Delvika, Yuana; Sutrisno, Sutrisno (INCODING: Journal of Informatics and Computer Science Engineering, 2024)
The 5S work culture is a work method created by Japan that implements the regulation and structuring of the work environment. One of the objectives of this study is to find out the design of 5S (Seiri, Seiton, Seisou, Seiketsu, and Shitsuke) in PT. Andalas Citra Elektrindo to observe the problems of working conditions so as to increase work efficiency and comfort. This study uses a descriptive research approach. The object of the research is on the production floor of PT. Andalas Citra Elektrindo which has not implemented 5S. The data collection technique was carried out using observation/observation techniques. Data obtained from direct observation on the production floor. The instrument used is to use a checklist instrument. The results of this research are the design of 5S work culture and the layout of the responsibility map of each department using Microsoft Visio 2016 software and the creation of 5S procedure forms.